Challenges of habitat mapping to inform marine protected area (MPA) designation and monitoring: An operational perspective. (January 2020) - Ware, Suzanne; Downie, Anna-Leena
Abstract: The UK has adopted a feature-based approach to MPA designation and monitoring to meet international and national obligations. Despite operational challenges, this approach is considered key to optimising conservation outcomes whilst making efficient use of limited resources. Drawing on lessons learnt from the UK's MPA Programme we discuss the practical issues which arise from: i) effective selection of conservation features identified as surrogates for biodiversity, ii) adequacy of feature representation across the MPA network and iii) implementation of quantifiable conservation objectives and ability to monitor progress in relation to them [4, 5]. There is recognition that high-level feature surrogates adopted for MPA designation may not adequately represent the full range of biodiversity present across UK marine habitats, and several of these features are indiscernible using acoustic mapping techniques. This results in our inability to accurately map their distribution and extent. Additionally, monitoring progress in relation to conservation targets is hampered by a lack of reliable indicators to assess change in their ecological status. Recommendations for the optimisation of MPA designation and monitoring using a systematic, evidence based approach are provided. These include: 1) flexibility in feature classifications to allow additional features to be designated as required, 2) communication of limitations in the evidence base to enable informed use in adaptive management decisions, 3) use of innovative technologies to more accurately map habitat features and 4) development of wider UK and regional sea scale monitoring programmes which align with an ecosystem based approach to the ongoing assessment of marine biodiversity. Highlights: Habitat mapping is a fundamental element of UK MPA designation and monitoring. Implementation of this approach is challenging due to incomplete coverage and uncertainty in existing maps. Habitat features selected for designation may not adequately represent the full range of biodiversity. Flexibility in classifications and innovative monitoring technologies are needed.